Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/brb3.2441
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of posterior cingulate cortex downregulation and symptom decreases in posttraumatic stress disorder and healthy individuals using real‐time fMRI neurofeedback

Abstract: Background Intrinsic connectivity networks, including the default mode network (DMN), are frequently disrupted in individuals with posttraumatic stress disorder (PTSD). The posterior cingulate cortex (PCC) is the main hub of the posterior DMN, where the therapeutic regulation of this region with real‐time fMRI neurofeedback (NFB) has yet to be explored. Methods We investigated PCC downregulation while processing trauma/stressful words over 3 NFB training runs and a transfer run without NFB (total n = 29, PTSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(60 citation statements)
references
References 125 publications
(255 reference statements)
6
57
0
Order By: Relevance
“…In a previously published analysis, we reported that individuals in the PTSD group showed reduced symptoms of reliving and distress in response to trauma-related stimuli over neurofeedback training (Nicholson et al, 2021), an effect not observed during the single-session rt-fMRI-NFB study targeting the amygdala (Nicholson et al, 2018;. While both groups were able to downregulate their PCC activity with similar success over neurofeedback training, downregulation was associated with unique within-PTSD group decreases in neural activity in several brain regions including those of the DMN (i.e., bilateral dmPFC, hippocampus) and SN (i.e., amygdala, mid-cingulate cortex) (Nicholson et al, 2021). Interestingly, these findings add to a growing body of research that highlight the critical involvement of the PCC in emotion regulation, including associations between normalized PCC activity and positive clinical outcomes following psychotherapy (Fresco et al, 2017;Garrett et al, 2019;Scult et al, 2019), as well as positive correlations between PCC-amygdala connectivity and PTSD symptom severity following trauma exposure Zhou et al, 2012).…”
Section: Restoring Dmn and Sn Connectivity In Ptsd With Neurofeedbackmentioning
confidence: 91%
See 4 more Smart Citations
“…In a previously published analysis, we reported that individuals in the PTSD group showed reduced symptoms of reliving and distress in response to trauma-related stimuli over neurofeedback training (Nicholson et al, 2021), an effect not observed during the single-session rt-fMRI-NFB study targeting the amygdala (Nicholson et al, 2018;. While both groups were able to downregulate their PCC activity with similar success over neurofeedback training, downregulation was associated with unique within-PTSD group decreases in neural activity in several brain regions including those of the DMN (i.e., bilateral dmPFC, hippocampus) and SN (i.e., amygdala, mid-cingulate cortex) (Nicholson et al, 2021). Interestingly, these findings add to a growing body of research that highlight the critical involvement of the PCC in emotion regulation, including associations between normalized PCC activity and positive clinical outcomes following psychotherapy (Fresco et al, 2017;Garrett et al, 2019;Scult et al, 2019), as well as positive correlations between PCC-amygdala connectivity and PTSD symptom severity following trauma exposure Zhou et al, 2012).…”
Section: Restoring Dmn and Sn Connectivity In Ptsd With Neurofeedbackmentioning
confidence: 91%
“…In the present analysis, our goal was to further examine how PCC-targeted fMRI neurofeedback may recalibrate connectivity within large-scale brain networks. In doing so, we were able to characterize neural mechanisms that might underlie improvements in emotion regulation among PTSD participants that were previously reported by our group (Nicholson et al, 2021) and also evaluate whether findings are convergent with that of previous EEG-based neurofeedback studies (Kluetsch et al, 2014;Nicholson et al, 2018). Given the accumulation of functional neuroimaging findings of altered DMN and SN activity in PTSD, as well as studies which have demonstrated a recalibration of DMN and SN connectivity as a function of successful neurofeedback treatment for PTSD, examination of functional connectivity between the PCC and key hubs of both networks was of particular interest in this study.…”
Section: Restoring Dmn and Sn Connectivity In Ptsd With Neurofeedbackmentioning
confidence: 93%
See 3 more Smart Citations